Development of electrochemical sensor based on thiolated calixarene/gold nanoparticle composite for lead and copper ions detection - Chong, Jin Mei (2021)
Heavy metal pollution is one of the global issues as the presence of excessive heavy metal in environment threaten both aquatic life and human beings. A selective and fast response sensor with a rapid detection method is urgent needed for the detection of heavy metal ions. Hence, this study used a thiolated calix[4]arene modified on gold nanoparticles and a screen-printed carbon electrode (TC4/AuNPs/SPCE) for Pb2+and Cu2+ determination. The modified electrodes were characterised via Fourier-transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS). The modified of thiolated calixarene/gold nanoparticle composite on screen-printed electrode was found enhancing the current response in Pb2+ and Cu2+ determination. Differential pulse anodic stripping voltammetry (DPASV) was used for the detection of Pb2+ and Cu2+ under optimum conditions. The limit of detection (LOD) for detecting Pb2+ and Cu2+ was 0.7982 × 10−2 ppm and 1.3358 × 10−2 ppm, respectively. Except for Zn2+ and Hg2+, the presence of competitive ions caused little effect on the current response when detecting Pb2+. However, all competitive ions caused a significant drop in the current response when detecting Cu2+, except Ca2+ and Mg2+, suggesting the sensing platform is more selective toward Pb2+ rather than Cu2+. The electrochemical sensor demonstrated good reproducibility and excellent repeatability with a low relative standard deviation (RSD) value in detecting Pb2+ and Cu2+. Most importantly, the result obtained in the analysis of Pb2+ and Cu2+ had a good recovery in river water, demonstrating the applicability of the developed sensor for real samples.